Price-Level Accounting and Scales of Measurement. - Moonitz, Maurice (The Accounting Review, 1970)
The article deals with the application of some of the elements of measurement theory to the problem of reporting the financial effects of price-level changes. Among other matters, measurement theory concerns itself with different "scales" of measurement and their interrelationship. There is a major concern related to the notorious shift in the exchange-value of money, country by country, decade after decade. In price-level accounting where one is trying to measure the change in the "exchange-value of money," the change in the unit employed in accounting to measure the power of money to command goods and services in the market. The means most frequently used to measure this change is an index of the level of prices in general. One further feature of scales of measurement is pertinent to the price-level problem in accounting. Furthermore, one should not underestimate the extent of the change required in the thinking habits of businessmen before one can expect enthusiastic acceptance of "price-level accounting."